2021
DOI: 10.4103/jcd.jcd_230_21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intracanal and extracanal heating on pulp dissolution property of continuous chelation irrigant

Abstract: Context: Extracanal and intracanal heating of sodium hypochlorite (NaOCl) improve its pulp dissolution, but limited literature is available on its effect as a combined single irrigant with etidronate. Aim: The aim of this study is to compare the effect of temperature on the effectiveness of NaOCl and continuous chelation protocol on the time required for the dissolution of vital and necrotic pulp. Materials and Methods: Dissolution time of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…EDTA was introduced in endodontics by Nygaard-Ostby in 1957. Today, 17% of EDTA solutions are associated with a detergent for greater flow [54,55].…”
Section: Edtamentioning
confidence: 99%
“…EDTA was introduced in endodontics by Nygaard-Ostby in 1957. Today, 17% of EDTA solutions are associated with a detergent for greater flow [54,55].…”
Section: Edtamentioning
confidence: 99%
“…in their study reported that pulp dissolution by continuous chelation was lower than hypochlorite even after warming. [ 16 ] Zollinger et al . stated that heating of NaOCl and HEDP is not beneficial as HEDP decomposes to acetic acid and phosphonic acid, which is neutralized by NaOCl.…”
Section: Discussionmentioning
confidence: 99%
“…The authors stated that NaOCl when mixed with HEDP retained its TDA at RT but lost its effect on heating to higher temperatures. [ 10 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…There are two ways to increase the temperature of irrigating solution: extracanal (heating of the solution before injection to the root canal) and intracanal (heating directly inside the root canal with heat carriers). According to research, intracanal heating of NaOCl is more efficacious than extracanal heating [50]. The former technique caused much better cleansing of the walls of the root canal from debris in comparison to the latter [51].…”
Section: Thermal Techniquesmentioning
confidence: 99%
“…One must bear in mind, that patients subjected to irrigation with EDDY complained about post-treatment pain more frequently than a group of patients treated with MDA. It might be related to the much more frequent pushing of irrigants through the apical foramen caused by using EDDY [50].…”
Section: Other Activation Systemsmentioning
confidence: 99%